Academic ESP Courses in a Hybrid Mode: Attitudes and Perceptions - Stefanova, Albena (English Studies at NBU, 2024)
Developing academic ESP courses in a hybrid mode has come to the forefront of the educational agenda due to social and economic reasons: technological advance followed by the emergence of new communication, business and education technologies; new generations of learners who grow up in virtual reality rather than in real life; commercialisation of education; changes in workplaces and business organisations; a pandemic that resulted in increased use of the electronic and hybrid modes of interacting and working. In light of these circumstances, the research on the key actors in the educational process – learners and teachers – has gained importance and has become the reason to initiate a study of these actors’ attitudes and perceptions with regard to the academic ESP courses in a hybrid mode. The article presents and discusses the results from a survey conducted within this study and related to the preparation of reference criteria for course design in terms of parameters. Data analysis has implications for the educational sector in terms of language and subject course development, as well as of the introduction of relevant policies in higher education.